Study of the prevalence of tobacco consumption among apparently healthy adult males in an urban area - Shafique Ahmed; Ravi A. Nimonkar; Vishal Sharma; Maninder Pal Singh Pardal; K. Rajiva (Journal of Family Medicine and Primary Care)
Background: Keeping in view the role of tobacco consumption as a modifiable risk factor in various diseases and gaps in scientific knowledge among the apparently healthy adult male population in India, the researchers chose to undertake this study. Materials and Methods: A cross-sectional study was conducted among apparently healthy adult males employed in various government offices to determine the prevalence of tobacco consumption. The minimum sample size to estimate a 95% confidence interval for the prevalence of tobacco consumption with 5% absolute precision was calculated to be 340. However, 500 subjects were included in the study. The tool used for data collection was the “personal interview technique.” Standard statistical methods were utilized for data analysis. Results: The overall mean age (standard deviation (SD)) of the study subjects was 30.96 yrs (4.32). Overall, the mean (SD) of number of years of tobacco use was 5.64 years (1.98). The mean (SD) of number of cigarettes smoked per day was 6.36 (3.09). The prevalence of current smokers showed a statistically significant increase from the age groups of 20–29 yrs to 50–59 yrs (P < 0.001). All subjects in the study were able to name at least three harmful effects of tobacco consumption. The overall mean amount spent on tobacco consumption per month was Rs 536.97 (1.44% of basic salary). Overall, the most common reason for smoking was peer pressure, where 40 (93.02%) gave this reason. Of forty-three tobacco users, 27 (62.79%) expressed a desire to quit tobacco consumption. The most common reason for expressing a desire to quit tobacco was the ill effects of tobacco consumption, where 23 (85.18%) tobacco users gave this reason. Conclusion: Our study on the prevalence of tobacco consumption among government employees provides an adequately clear picture of this public health epidemic in India. There is an immediate need for target group-specific policies for tobacco control, which should be integrated with the relevant national health programs at all levels.